2018
DOI: 10.1051/e3sconf/20184400127
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of lakes as a component of small retention in Wielkopolska

Abstract: Abstract. In the context of the observed climatic changes, unfavourable extreme situations occur increasingly frequently, manifested by, among others, the occurrence of droughts and floods. In the case of Poland, the central part of the country, in administrative terms covering the Wielkopolskie Province, is considered a region with a deficit of water resources. Such a situation was and is determined by a combination of natural and artificial factors. The former ones result from low precipitation and high air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This situation resulted in the government’s actions aimed at increasing retention. An important element of this programme relates to lakes, which aims to ensure growth and stability of water resources through artificial water layering (Nowak & Ptak, 2018). However, an increase in evaporation has already been an important element modifying the water resources of lakes (Ptak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This situation resulted in the government’s actions aimed at increasing retention. An important element of this programme relates to lakes, which aims to ensure growth and stability of water resources through artificial water layering (Nowak & Ptak, 2018). However, an increase in evaporation has already been an important element modifying the water resources of lakes (Ptak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the time of progressing climate change, particular attention should be paid to the fact that Poland is one of the countries with the smallest water resources in Europe [98]. Therefore, in the light of the declining lakes water resources observed [99], it is really important to monitor the fluctuations in lakes water levels and to determine their causes for the purposes of rational and effective water management.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from experience with other lakes situated in west and central Poland, damming waters in lakes not only prevents the loss of water resources in a water body itself and in its catchment basin, but it also allows the flow to be stabilised in the river that drains the dammed lake (Nowak, Grześkowiak 2010;Nowak et al 2011b;Grześkowiak et al 2012; Nowak, Ptak 2018a). The sense of damming lakes and the benefits thereof are emphasized by Jańczak et al (2004), who indicated the retention possibilities of selected lakes in Poland, and by Nowak and Ptak (2018b), who pointed out the high potential for water retention in the lakes of the region of Wielkopolska. Lake damming is also successfully used in the realization of the Small Retention Program, especially by the former Provincial Boards of Amelioration and Hydraulic Structures and by the National Forests.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape is dominated by sandy-loamy frontal moraine hills dissected by a network of glacial channels and river valleys. The substrate is dominated by loams and ablation sands in the south part of the catchment basin, and boulder loams in the central and north parts (Nowak 2018). Against the background of the climate conditions of Poland, the area under discussion is characterized by one of the lowest sums of annual precipitation (<550 mm · year -1 -on the basis of data of the Institute of Meteorology and Water Management -National Research Institute (IMWM-NRI)) and a high potential evaporation, amounting to an average of over 600 mm · year -1 (Kędziora 2008;Przybyłek, Nowak 2011a;Ilnicki et al 2012a, b).…”
Section: Study Areamentioning
confidence: 99%